1987
DOI: 10.1007/bf02388159
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal stenosis with esophageal atresia

Abstract: Esophageal atresia with tracheosophageal fistula may be associated rarely with distal esophageal stenosis. Three patients are reported with this combination of esophageal anomalies. In addition the clinical and radiologic features of 24 patients previously reported in the literature are reviewed. Careful evaluation of the distal esophagus during postoperative contrast studies in patients with esophageal atresia should be obtained to exclude distal stenosis. The presence of unrecognized distal esophageal stenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The EA with CES group had fewer cardiac and more anorectal anomalies (Table 1 ). Some previous studies suggested that EA-associated CES might result in increased postoperative complications at the anastomotic site [ 10 , 15 , 21 ], although a more recent study, like our own, experienced no such cases [ 4 ]. The disease duration in patients with EA-associated CES, defined as days from the first symptom to the last treatment session, was significantly longer than in patients with EA and AS, suggesting that CES was more refractory to dilatation than AS (Table 3 ).…”
Section: Discussionmentioning
confidence: 68%
“…The EA with CES group had fewer cardiac and more anorectal anomalies (Table 1 ). Some previous studies suggested that EA-associated CES might result in increased postoperative complications at the anastomotic site [ 10 , 15 , 21 ], although a more recent study, like our own, experienced no such cases [ 4 ]. The disease duration in patients with EA-associated CES, defined as days from the first symptom to the last treatment session, was significantly longer than in patients with EA and AS, suggesting that CES was more refractory to dilatation than AS (Table 3 ).…”
Section: Discussionmentioning
confidence: 68%
“…We presume that the ETT was similarly placed into the diverticulum during our intubation attempts (Figs. [1][2][3][4][5].…”
Section: Case Presentationmentioning
confidence: 98%
“…It is not uncommon for the repaired esophagus or trachea to become stenotic at the repair site later in life. 1 If the child becomes symptomatic, an esophagogastroduodenoscopy (EGD) or esophagogram is required to diagnose and determine the severity of the esophageal stenosis. Other possible complications from the TEF or its repair include tracheomalacia, vocal cord paralysis, gastroesophageal reflux, an anastomotic leak, esophageal rupture, reoccurrence of the fistula, and esophageal dysmotility.…”
mentioning
confidence: 99%